STUDI PENGARUH RUGI-RUGI TRANSFORMATOR DAYA TERHADAP EFISIENSI TRANSFORMATOR DAYA 60 MVA DI PT PLN (PERSERO) GI BABAT - M.Khusni Mubarok; Hadi Tasmono (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
As time goes by, development.Technology is growing rapidly. Life today is all modern and is needed as a source of electrical energy. The increasing need for electrical energy requires the availability of reliable and efficient electrical energy. PT. PLN (Persero) has three levels in the distribution of electricity, including the generation rate, transmission rate and distribution level, causing many problems that occur in it. Problems that occur among them are in power transformers there are power losses caused by several factors. Power losses that occur in power transformers need to be considered, because they can cause a considerable loss of efficiency. Analysis of the calculation of power losses was carried out on a 150 kv high-voltage system at the tripe substation to a 20 kv distribution line. The study was carried out by asking permission from PT. PLN (Persero) Substation tripe and then collect the required data such as power transformer specifications, peak load data and Kwh sales data for a period of 1 year starting from January 2022 to December 2022. The conclusion of the study of the effect of total losses (technical and non-technical losses) on efficiency is that there is a relationship between loads, losses and transformer efficiency. So it can be concluded that the load is directly proportional to the losses of the transformer and inversely proportional to the efficiency of the transformer. If the greater the load, the greater the total losses. So that efficiency is also decreasing,